Conselhos Ambientais: Uma análise do processo de participação de conselheiros municipais no Território Açu-Mossoró–RN - Morais, Lucas Andrade de (Universidade Federal Rural do Semi-Árido, 2017)
The 1988 Federal Constitution, by ensuring the creation of participatory institutions, legitimized popular participation in public management decision-making processes. In the environmental field, the Municipal Environmental Councils present themselves as a space for ecological protection by promoting the decentralization of decision-making power, access to information and control of management actions and environmental policies. In this sense, the research proposed to analyze the process of participation in the Municipal Councils of Environment in the Territory Açu-Mossoró (RN). For this purpose, a qualitative, descriptive, bibliographic, documentary and field study was carried out. The research site was the Councils active in the municipalities of the territory. The data were collected through an interview with a semistructured script, composed of 47 (forty seven) questions, together with five titular directors. The documentary research was done by the analysis of minutes of meetings, resolutions and legislations from the years of 2009 to 2015. The interviews and the documents were analyzed by the Excel Program, Software Nvivo and by the method of the interpretative technique. A preliminary survey showed that only in the municipality of Mossoró (RN) there was active Environmental Council. Thus, analysis of the participation in the Councils started from three dimensions: legal, formal and the conception of the interviewees. In the legal dimension (resolutions and laws) an ideal participation is granted with evidence in control, partnership, co-management, delegation, interactive or collaborative. The formal dimension and the conception of the interviewees corroborate and present a type of participation divergent to what is established in the legal dimension, being mainly of control and functional. The Council presented some problems that need to be strengthened in its participatory process, such as: the choice of members with an interest / vocation to participate in the Council, the party question, the interest of groups, influence of the government in the Council, local elite dominance, asymmetries of Representations in the decision-making process, formation, structuring and composition of the Council that gives rise to rigging, discontinuance of meetings, lack of interest, lack of attendance and availability of members' time, lack of training and continued environmental education for members, lack of publicity, publicity And transparency of Council actions, lack of physical space and lack of access to information and data in a timely manner. Such difficulties and limitations have hampered the performance of the directors in a way that provides an ideal participation
Environmental Councils: An analysis of the process of participation of municipal councilors in the Açu-Mossoró-RB Territory
Keywords: Participação popular; Meio ambiente; Conselhos ambientais; Municípios; Território Açu-Mossoró; Popular participation; Environment; Environmental advice; Counties; Territory Açu-Mossoró; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE